ANALISA PENGARUH EXPERIENTIAL MARKETING TERHADAP LOYALITAS KONSUMEN MELALUI KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING DI STARBUCKS COFFEE JOGJA CITY MALL - Arif Setiawan (MNJ 16 UMY 239, 2016)
This research aimed at finding how much the influence of experiential marketing to the satisfaction of consumers, experiential of marketing for the loyalty of consumers, the satisfaction of consumers against the loyalty of consumers and the satisfaction of consumers play a role as variable intervening between experiential the marketing with the loyalty of consumers. The sample collecting method used was purposive sampling. The respondents in the study were 150 customers Starbucks Coffee Jogja City Mall. Ther research also used Structural Equation Modelling (SEM) conducted throught AMOS 21.0 program as the analysis tool. The result of the research showed that the experiential of marketing has a positive influence and significantly to the satisfaction of consumers, experiential of marketing has a positive influence and significantly affect the loyalty of consumers, then the satisfaction of consumers have a positive influence and not significantly affect the loyalty of consumers and the satisfaction of consumers do not play a role as variable intervening between experiential the marketing with the loyalty of consumers. Keywoeds: experiential marketing, consumers satisfaction, consumers loyalty